Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/jdv.15388
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopic evaluation of melanocytic nevi changes after photo‐epilation techniques: a prospective study

Abstract: Background The clinical and dermoscopic changes of melanocytic nevi under the effects of photo‐epilation are poorly known. Objective Prospective study on clinical and dermatoscopic effects of photoe‐pilation on melanocytic nevi. Methods Eighteen patients exposed to photo‐epilation gave consent to a follow‐up programme from 2008 to 2017 at the Videodermatoscopic Office of the Dermatology Clinic of Cagliari (Italy), with clinical and dermoscopic assessment. Results A mean 2‐year follow‐up was recorded for 73 les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(31 citation statements)
references
References 12 publications
3
26
1
Order By: Relevance
“…These findings are in consistent with the study of Guicciardi et al that reported any degree of pigment network change in 79% of cases. 13 Additionally, in the present study, we observed that nevi became lighter in 43.9% and darker in 19.7% of cases. Guicciardi et al reported loss of pigmentation in 82% of nevi but also an increase in pigmentation at the periphery with central light brown background in most of the cases.…”
Section: Discussionsupporting
confidence: 63%
“…These findings are in consistent with the study of Guicciardi et al that reported any degree of pigment network change in 79% of cases. 13 Additionally, in the present study, we observed that nevi became lighter in 43.9% and darker in 19.7% of cases. Guicciardi et al reported loss of pigmentation in 82% of nevi but also an increase in pigmentation at the periphery with central light brown background in most of the cases.…”
Section: Discussionsupporting
confidence: 63%
“…Only one case showed progressive growth 23 . The authors noted that although malignant nevus modifications after photoepilation have not been described, the potential long‐term side effects of photoepilation on melanocytic nevi remain unknown 23 Unintentional exposure of the tattoo pigment to the beam during laser treatment can also cause complications. …”
Section: Etiological Classification Of Laser Complicationsmentioning
confidence: 99%
“… Unintentional effects of laser radiation on skin pigmented lesions (melanocytic nevi, tattoo pigment): Guicciardi et al published the prospective study on clinical and dermatoscopic effects of photoepilation on melanocytic nevi 23 . The most frequently reported clinical change was the color of the nevus, which was sharper than the main images, sometimes with increased pigmentation at the periphery or residual patches of pigmentation with disappearing borders.…”
Section: Etiological Classification Of Laser Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to study the morphological changes of MN treated with Nd:YAG laser or IPL for photo‐epilation, Guicciardi et al . described dermatoscopic changes of the appearance (73 MN in 18 patients with a mean 2‐year follow‐up) in this issue.…”
mentioning
confidence: 99%